(3GdJLGQI GdGdcJQhfjI hGdCYeGd GdGdcJQhfjI ef efXhQ Jbfj hJLGQj hEOGQj (B/s - (3GdWjWj, NVQ eUHGMs ((3YeGf(B: s (3OGQ GdMGeO ddfTQ hGdJhRjY(B, s, 2008)
(3ebOeI Edi GdJLGQI GdGdcJQhfjI hGdCYeGd GdGdcJQhfjI,JbfjI GdJLGQI GdGdcJQhfjI,GdJShjb YHQ GdEfJQfJ,EOGQI GdYdGbI eY GdRHGFf EdcJQhfjG,CfXeI GdOaY GdeGdj GdEdcJQhfj,GdMcheI GdEdcJQhfjI,SdSdI GdEeOGO GdGdcJQhfj,GdeRGOGJ hGdYWGAGJ GdGdcJQhfjI,Cef GdJLGQI GdGdcJQhfjI,GdCOhGJ GdeSJNOeI aj JUeje ehGbY GdJLGQI GdEdcJQhfjI,JUeje ehGbY fGLMI ddJLGQI GdEdcJQhfjI,bVGjG CNdGbjI hbGfhfjI JJYdb HGdJLGQI GdEdcJQhfjI,GdbGfhf GdOhdj ddJLGQI GdEdcJQhfjI hWQb MeGjJgGs
(3HHdjhZQGajG(B:(3U(B.434s
Keywords: (3GdJLGQI GdGdcJQhfjIs; (3GdJLGQI GdNGQLjIs